THE ANALYSIS OF SEMANTIC GRAMMATICAL ERRORS IN VARIOUS ARABIC TRANSLATIONS - Shofa Musthofa Khalid; Anwar Sanusi; Deni Maulana; Tatang Tatang; Mohamad Zaka Al Farisi (Arabi : Journal of Arabic Studies, 2021)
This study aimed to reveal the semantic grammatical errors in the translation of various Arabic sentences into Indonesian. This study used a qualitative descriptive method with a content analysis model. The data sources in this study were five different Arabic sentences translated by the teacher who taught the heritage book in Islamic boarding schools, namely: jumlah muṡbatah (positive sentences), jumlah manfiyah (negative sentences), jumlah istifhamiyah (interrogative sentences), jumlah syarṭiyah (conditional sentence), and jumlah al-qasam (sentence of oath). After analyzing and discussing the data obtained, the researcher found that there were 70% morphological errors in the translated text results consisting of 51% noun errors (isim) and 19% verb errors (fi'il). Additionally, the researcher found 76% syntactic errors from the translated text, consisting of 10% word errors, 9% phrase errors, 29% clause errors, and 28% sentence errors.